The Effects of Task Type on Time to Task Failure During Fatigue: A Modified Sørensen Test. Issue 1 (2nd January 2018) - Russ, David W.; Ross, Andrew J.; Clark, Brian C.; Thomas, James S.
ABSTRACT: Understanding mechanisms of fatigue of the trunk extensors is important because fatigue is a major factor in predicting incidence of low back pain, but few studies have examined trunk extensor fatigue muscles using differing load types and measured the amplitude and frequency domain of the electromyographic signal to explain these differences. Sixteen healthy participants performed position- and force-matching fatigue tasks in a modified Sørensen test position. Time to task failure was significantly longer during the position-matching task compared to force-matching task (58.3 ± 6.6 min vs. 36.1 ± 5.4 min). This finding is the opposite of that commonly reported for the appendicular muscle, but the mean power frequency shifts and muscle activation patterns of the trunk and hip extensors did not explain this difference. The mean power frequency shifts and muscle activation patterns of the trunk and hip extensors did not explain this difference. The greater time to task failure during the position-matching task may reflect adaptation of the trunk extensor muscles to optimize maintaining specific joint angles more so than specific loads.